Biceps tendon augmentation in arthroscopic partial repair of irreparable massive rotator cuff tears: a systematic review and meta-analysis - Evan M. Polce, MD; Kyle N. Kunze, MD; Jake Koehler; Michael C. Fu, MD, MHS; Samuel A. Taylor, MD; Lawrence V. Gulotta, MD; David M. Dines, MD; Joshua S. Dines, MD (JSES International, 2025)
Background: There remains debate as to whether augmentation of large and massive irreparable rotator cuff tears (MIRCTs) with long head of the biceps tendon (LHBT) in the setting of arthroscopic partial repair (PR) confers a clinical benefit. The purpose of the current study was to synthesize population-level data from the current literature to determine whether LHBT augmentation for PR of MIRCTs reduces the incidence of re-tears and improves clinical outcomes compared with PR alone. Methods: The PubMed/MEDLINE, Embase, OVID, and Cochrane Libraries were queried in April 2024 for trials directly comparing PR with PR with LHBT augmentation for MIRCTs. Information pertaining to diagnostic imaging indices (Goutallier grades), patient-reported outcome measures, range of motion, and adverse events (re-tear rate, reoperations, complications, conversion to arthroplasty) were recorded when reported. DerSimonian-Laird random-effects models were constructed to quantify effect estimates for categorical and continuous outcomes, represented as pooled incidence and standardized mean differences with associated confidence estimates, respectively. Results: Six studies encompassing the outcomes of 367 patients (PR: n = 188, 51.2%; PR + LHBT: n = 179, 48.8%) were included. The mean age and follow-up among included studies ranged from 59.5-69.3 years and 20.5-39.9 months, respectively. The pooled incidence of re-tears was lower in the PR with LHBT augmentation group compared with PR alone, but not statistically significant (38% vs. 52%, P = .26). There were no significant differences in any range of motion parameters between the groups at the final follow-up (all P > .05). Of 4 patient-reported outcome measures amenable for meta-analysis, the University of California-Los Angeles score was the only metric in which a significant difference was observed, favoring the PR with LHBT augmentation cohort (30.2 vs. 32.6, P < .01); no statistically significant between-group differences were demonstrated for American Shoulder and Elbow Surgeons, VAS pain, or Constant-Murley scores (all P > .05). There were no significant differences in mean postoperative acromiohumeral interval between groups (P = .11). Conclusion: Among patients undergoing arthroscopic PR of MIRCTs, LHBT augmentation did not result in superior clinical outcomes compared with PR alone. Although the 14% reduction in the incidence of re-tears observed with LHBT augmentation was not statistically significant, it may represent a clinically important difference.